ANALISIS FAKTOR-FAKTOR KEDISIPLINAN KERJA KARYAWAN PADA KOPERASI TIRTA DHARMA KHATULISTIWA PDAM KOTA PONTIANAK - Sianipar, Pesta Aisawara (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to understand the factors analysis work discipline employees at cooperatives tirta dharma khatulistiwa PDAM kota pontianak . The methodology that was used in this research that is a method of descriptive with a qualitative approach. Data sources in this research are managers and 3 employees consisting of (unit shops 1 employees, a savings and loan unit 1 employees, unit instalatir / construction 1 employees ). Data were collected based on interview guidelines as well as the results of sheets note and documentation . Testing the validity of data in this research namely by triangulansi source. The results of the study showed that discipline work employees at cooperatives tirta dharma khatulistiwa pdam kota pontianak is good can be seen from 5 an indicator for discipline work employees at cooperatives tirta dharma .Based on the results of research conducted in cooperatives tirta dharma khatulistiwa PDAM kota pontianak researchers give suggestions to make employees increase discipline that this type of cooperatives can more advanced and able to compete with the other business .Keywords: Factors discipline work employees cooperativesÂ